Adoption of Information Technology Among Manufacturing Firms in Tampoi, Johor - Hee, Catherine Chia Lin (2008)
The purpose of this study is to examine the extent of information technology adoption among manufacturing firms located in Tampoi, Johor. This study examines the likelihood of information technology adoption based on CEO characteristics, organization characteristics, information technology characteristics and environmental characteristics in order to identify the extent of information technology adoption in manufacturing firms. The identification of factors that contribute most to information technology adoption deepens current understanding of how effective information technology planning is being carried out in firms. Such findings are necessary and lay the foundation for the eventual development of effective information technology adoption strategies for firms. The findings show that factors that influence the adoption of information technology include CEO characteristics and organizational characteristics. This study concludes that regardless of the firm size, CEO innovativeness, CEO attitude towards adoption of information technology and CEO information technology knowledge are essential determinants to the adoption of information technology in manufacturing firms.